(untitled) (INNOVATIVE ECONOMY, 2020)
Piata L.V. BASIC APPROACH TO STRATEGIC PLANNING OF INVESTMENT ACTIVITIES OF BUSINESS ENTITIES IN AGRICULTURAL SECTOR Purpose. The aim of the article is to highlight the basic approach to strategic planning of investment activity of business entities in agricultural sector and its main components. Methodology of research. The main research methods in the article are analysis and synthesis methods. Using the analysis method, the components of the basic approach to strategic planning of investment activity are analysed. Using the synthesis method, significant elements of the studied basic approach are determined. Findings. The article discusses the basic concepts used in the process of strategic planning of investment activity of business entities in agricultural sector, in particular: “investment”, “investment activity”, “planning”, “strategic planning” and “strategic planning of investment activity”. The specialities of planning and strategic planning of investment activity in the business entities in agricultural sector are described. Peculiarities of planning and strategic planning of investment activity in economic entities of the agricultural sector are described. Originality. The author defines the main components of the basic approach to strategic planning of investment activities of business entities in agricultural sector: functional specialities, industry differences, principles, criteria, structural elements, sources of investment, stages. The attention of agricultural entities is emphasized on the importance of flexible application of the basic approach in the process of strategic planning of investment activity, taking into account the specialization of their economic activity, the level of material and technical support, the actual and potential ratio of investment sources, the influence of environmental factors and specific development goals. Practical value. The results of the study can be used in the process of preparing strategies and strategic plans for investment activities by agricultural entities. Key words: investments, investment activity, planning, strategic planning, investment activity strategies.